OPTIMASI PERTUMBUHAN DAN POTENSI ANTAGONISTIK Bacillus pumilus TERHADAP PATOGEN Xanthomonas campestris SERTA IDENTIFIKASI MOLEKULER GEN PENYANDI PKS DAN NRPS - Laila Nur Faizah; Anto Budiharjo; Endang Kusdiyantini (Jurnal Akademika Biologi, 2017)
Xanthomonas campestris is one of the broccoli pathogen that difficult to be eradicated. B. pumilus is a prospective biocontrol agent due to its ability to produce antibiotical subtances that inhibit the growth of pathogenic bacteri and fungi. Beside that, B. pumilus have a great endurance to extreme environment by its ability to form spores. Some species of Bacillus genus have been reported to have PKS (Polyketide Synthetase) and NRPS (Non-Ribosomal Peptide Synthetase) coding gene which is a mega shyntetase that have a role in the production of antibiotic subtances. This reseach aims to test the inhibitory potency of B. pumilus toward X. campestris, identify the PKS and NRPS coding gene and to knwing the optimum growth of B. pumilus on the medium with different pH and carbon source. Reseach is conducted with Completely Randomized Design (CRD) with three replications on two growth parameters that is pH and carbon source. pH treatment is conducted with pH 5, 6, 7, and 8, while carbon source treatment is conducted with glucose, fructose, and sucrose as the carbon source. The obtained result is analized with ANOVA with significant level of 95%. The result shows B. pumilus ability to inhibits the growth of X. campestris producing inhibitory zone with 1,84 mm of diameter. The reseach showed negative result in NRPS coding gene detection and a positive result in PKS coding gene. PKS coding gene identification which is analized with BLAST shows 98% homology with PKS coding gene of Bacillus subtilis HNS005. Growth optimization shows the optimum groth of B. pumilus at pH 6 and glucose as the carbon source.Keywords: biocontrol, B. pumilus, PKS, NRPS, growth optimization